1986
DOI: 10.1093/ptj/66.3.351
|View full text |Cite
|
Sign up to set email alerts
|

Actions of Hip Muscles

Abstract: This article describes and explains the moment arm vector (MAV) concept, uses the concept for the quantitative classification of hip muscles according to action, and applies the findings to selected clinical problems. A three-dimensional, straight-line model of hip musculature was used. Measurements made on a matched, dry bone specimen provided muscle attachment point location data for the model. Straight lines of muscle action between attachment sites were simulated for a variety of hip configurations during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
131
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(138 citation statements)
references
References 0 publications
7
131
0
Order By: Relevance
“…7(D)) ranged from −2.0 to 2.0 cm. For both of the gluteal muscles, the hip flexion moment arms determined experimentally 20 varied more with hip flexion than the moment arms computed with the 3D models. The peak hip adduction moment arms for the gluteus maximus fibers (Fig.…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…7(D)) ranged from −2.0 to 2.0 cm. For both of the gluteal muscles, the hip flexion moment arms determined experimentally 20 varied more with hip flexion than the moment arms computed with the 3D models. The peak hip adduction moment arms for the gluteus maximus fibers (Fig.…”
Section: Resultsmentioning
confidence: 79%
“…7(C)). Previous experiments, 20 which represented gluteus maximus with a single line of action, had a single peak moment arm that was slightly larger than the largest 3D model fiber moment arm. The peak hip extension moment arms for the gluteus medius fibers (Fig.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…This decrease in RF specificity of muscle action is attributed to the biarticular nature of the muscle (i.e., it acts at both the knee and hip joints) and its secondary action as a hip abductor, 30 which was clearly visible in many of our subjects. Significantly higher specificity was observed in the VL and VM muscles of dominant limb (right) of our subjects.…”
Section: Discussionmentioning
confidence: 78%
“…This finding might result from the increase in MA of the internal rotators and reversal of the rotary action of some of the external rotators 1) . Dostal et al 5) reported that although there are no primary or assistant hip internal rotators in the anatomical position, the anterior and middle fibers of the gluteus medius and minimus muscles work as hip internal rotators at 40° of hip flexion. In addition, posterior fibers of the gluteus medius and minimus and piriformis muscles also work as hip internal rotators at 90° of hip flexion.…”
Section: Discussionmentioning
confidence: 99%